Power System Transient Current Sensor Based on Magnetoresistance Effect. Issue 1 (February 2021) - Bi, Lanxi; Wu, Mengke; Xu, Linbo; Sun, Shihang; Yu, Kun; Zeng, Xiangjun
Abstract: Aiming at the problem that the mixed use of overhead lines and cables causes serious refraction and attenuation of the traveling wave signal in propagation, which makes the traditional traveling wave sensor unable to adapt to the weak signal identification and recording requirements. A wideband sensor for detecting transient current signal of power system is developed. The detection principle of the anisotropic magnetoresistive sensor is analyzed, and the tiny signal precision differential amplifier circuit is designed. Based on the actual situation of the power system, a corresponding test environment was built to conduct transient current transfer tests. The experimental results show that the sensor has a high linearity in the 0-5MHz bandwidth, and is suitable for the extraction of various transient signals, especially in the power system traveling wave protection has high application value.